Supply chain transformation : practical roadmap to best practice results - Sherman, Richard J., 1950- (Wiley corporate F & A series., 2013)
BAchieve best practices in supply chain management/b Much is being written about global supply chain and sourcing options emerging in today's marketplace. Transforming supply chain management to achieve operations excellence is a mandate for many companies globally. iSupply Chain Transformation/i walks you through this potentially difficult process and gets you started on the journey. Much more than just a how-to book, it's a why-to book that is as compelling for any business person as it is for supply chain management professionals. This book provides an invaluable road map to companies looking to transform their supply chains and organizations to achieve best practice results, beginning with guidance onhow to make the case for change. Change is inevitable; growth is optional.ulliIncludes real world cases and illustrations/liliOffers a step-by-step road map to transforming your supply chain/liliExplains ihow/i to obtain "senior management" commitment to transformation/liliCovers sourcing, production, and logistics process integration points with product development, marketing, sales, and finance processes as well as emerging technologies (RFID, Cloud computing, telematics, ERP, GPS/LBS & others)/li/ul One of the biggest hurdles to supply chain transformation is overcoming a culture that is resistant to change. iSupply Chain Transformation/i helps you understand the cultural resistance and evaluate where change is needed most, and then develop the game plan for overcoming resistance to achieve best practice results.